3D CFD Simulation and Experimental Validation of Small APC Slow Flyer Propeller Blade - Ahmed Kutty, Hairuniza; Rajendran, Parvathy (MDPI, 2017)
The current work presents the numerical prediction method to determine small-scale propeller performance. The study is implemented using the commercially available computational fluid dynamics (CFD) solver, FLUENT. Numerical results are compared with the available experimental data for an advanced precision composites (APC) Slow Flyer propeller blade to determine the discrepancy of the thrust coefficient, power coefficient, and efficiencies. The study utilized unstructured tetrahedron meshing throughout the analysis, with a standard k-! turbulence model. The Multiple Reference Frame model was also used to consider the rotation of the propeller toward its local reference frame at 3008 revolutions per minute (RPM). Results show reliable thrust coefficient, power coefficient, and efficiency data for the case of low advance ratio and an advance ratio less than the negative thrust conditions.